Management diversity and human resources policies and practices in high education institutions - Lucas dos Santos, Geneia; Lisboa Gaspar, Fabio; Rodrigues, Maria Beatriz; Baldissarelli, Juciele Marta (Revista de Administração da UFSM, 2020)
This article investigates the perception of the workers in High Education Institutions (HEIs) in the State of Santa Catarina (SC), it is based on six Human Resources policies, under the perspective of generational diversity. The research’s nature was quantitative, based on description and survey. Data collection was carried out using the scale of the Human Resources Policies and Practices (EPPRH), validated in Brazil by Demo in 2008. A total of 409 workers from eleven HEIs participated in the study. Comparatively, results were very similar, with averages close in the items investigated, comparing the generations baby boomers, X, Y e Z. It can be sustained that in the HR policies and practices in HEIs all generations usually converge on the thinking and perceptions related to them. The interviewees showed indifference or unawareness about the policies that were studied, since their existence and/or effectiveness were not expressly perceived, it would be advisable for HEI to re-think their proposals, models of implementation and dissemination of these themes. Further research is suggested in view of differences in the belonging of HEI workers, intersectionalities of diversity, and qualitative understanding of responses.